Understanding the demand for “protective foods” in East Africa: An economic analysis with recommendations - Headey, Derek D.; Ecker, Olivier; Comstock, Andrew R.; Ruel, Marie T. (International Food Policy Research Institute, 2021)
Suboptimal diets are a major risk factor for avoidable death and disease in low- and middle-income countries. Evidence shows that some foods or food components (e.g., processed red meat, saturated fat, salt, sugar) significantly elevate the risk of noncommunicable diseases and mortality, while others protect health (e.g., vegetables, fruits, pulses, nuts/seeds, fish, whole grains—referred to in this document as “protective foods”). We used household surveys to compare dietary patterns in Ethiopia, Kenya, Tanzania, and Uganda to the EAT-Lancet healthy reference diet and to quantify and explain consumption gaps for nutritious foods. Compared to the EAT-Lancet healthy reference diet, consumption gaps for pulses and nuts/seeds, vegetables, and fruits are large for both poor and rich consumers in rural and urban areas in the four countries studied, while consumption gaps for meat, fish, and eggs and dairy foods are much larger for lower income groups. Food expenditures of most households in these four countries are far too low to allow consumption of the healthy reference diet; animal-source foods and vegetables are the largest cost components of food expenditures, although quantities consumed of both food groups are much lower than the EAT-Lancet healthy reference diet. Income elasticities of demand for pulses and nuts/seeds and vegetables are often low or moderate, suggesting weak consumer preference for these foods, while income elasticities for fruits and animal-source foods are relatively high. Income growth alone will not solve dietary problems in East Africa; in addition to supply-side interventions to improve affordability, special interventions are required to increase consumer demand for underappreciated protective (nutritious) foods such as pulses and nuts/seeds and vegetables.